The Degree of Implementation of Waste Management on Ship - Montallana, Derek Mar; Mausisa, Herminigildo; Aquino, Renz Ian; Balacuit, Jade Nathaniel; Menil, Feldan; Roferos, Marc Leo; Yaon, Jezryll (JPAIR Multidisciplinary Research, 2024)
Ships generating waste pose a significant environmental challenge in the maritime sector. This research aims to assess how effectively waste management practices are implemented by maritime personnel to mitigate the environmental impacts of onboard waste. Data gathered from survey questionnaires were analyzed using a quantitative research design, focusing on responses from chief officers and second engineers of ships. A four-point Likert scale was employed, and results were evaluated using frequency percentages, weighted means, and the Chi-square statistical analysis. The study aimed to profile the ship's crew and evaluate the implementation of waste management strategies, particularly regarding waste management plans and waste disposal onshore and ship-to-shore. The findings indicate that waste management implementation at the Port of Surigao's ships was fully achieved. These results underscore the importance of comprehensive waste management systems and training to ensure consistency in perceptions and practices among maritime officers. Therefore, the researchers suggested that ship operators can reduce environmental impact and promote sustainability in the maritime industry by developing a comprehensive waste management plan, providing crew training, installing effective waste segregation facilities, implementing recycling initiatives, and conducting regular audits.
Keywords: Ship Waste; Management; Degree; Implementation; Disposal; Management Plan; Quantitative; survey; Surigao City; policy development; Philippines; Asia